Insights into the effects of dynamic high-pressure microfluidization on the structural and rheological properties of rapeseed protein isolate. (August 2022) - Zhang, Nan; Xiong, Zheng; Xue, Wenyi; He, Rong; Ju, Xingrong; Wang, Zhigao
Abstract: The application of dynamic high-pressure microfluidization (DHPM) provides interesting modifications in food structures. However, the effects of DHPM on the structural and rheological properties of rapeseed protein isolate (RPI) were scarcely investigated. In this study, the average hydrodynamic size of RPI treated by DHPM significantly declined from 239.2 nm to 170 nm with the pressure and time rising to 60 MPa and 2 min. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis found that DHPM did not affect the molecular mass of the RPI. The changes in the intrinsic fluorescence and circular dichroism spectra showed that tertiary and secondary structures of RPI were altered, as proved by the higher fluorescence intensity and greater conversion of random coils and β-sheets into α-helices compared with the control (unprocessed RPI). The spatial unfolding of the RPI structure and the dissociation of chemical bonds influenced its rheological behavior. All RPI suspensions (15%, w / v ) processed by DHPM had lower apparent viscosity, moduli, higher gelling temperature (up to 69.7 °C) than control, and the differences in rheological performance were closely dependent on the treatment pressure and time. In conclusion, through this study of the effects of DHPM on RPI, DHPM was shown to be a potential method for modifying proteins and reducing the consistency of high-protein fluid foods. Highlights: Dynamic high-pressure microfluidization (DHPM) altered rapeseed protein isolate (RPI). DHPM treatment reduced the particle size of RPI and altered its spatial conformation. Apparent viscosity of RPI dispersions (15%, w / v ) treated by DHPM decreased sharply. DHPM treatment delayed the gelling temperature of RPI dispersions (15%, w/v).